STRATEGI PENGUATAN KELOMPOK PETERNAK KAMBING DOMBA DI DUSUN KEMENDUNG, DESA PENANGGUNGAN, KECAMATAN TRAWAS - Riyanto Riyanto; Novita Dewi Kristanti; Gita Dwi Andritaningrum (STKIP Pesisir Selatan, 2026)
Livestock farmer groups play a crucial role in improving productivity, business management, cooperation, and the sustainability of goat and sheep farming operations. However, these groups still face various institutional challenges, such as suboptimal administration, a lack of legal status, and farming systems that remain conventional. This study aims to analyze internal and external factors, formulate strengthening strategies, determine priority strategies, and evaluate the effectiveness of these strategies for the Mendho Joyo Livestock Group in Kemendung Hamlet, Penanggungan Village, Trawas Subdistrict. The study employed a quantitative descriptive method involving 24 respondents through interviews, observations, and surveys. Data analysis was conducted using IFAS, EFAS, SWOT, QSPM, and a strategy effectiveness evaluation. The results indicate that the group is in Quadrant I (SO), with positive strengths and opportunities. The priority strategy is to leverage the group’s complete and active management structure to secure support from the government, the Agricultural Extension Agency (BPP), and stakeholders, with a QSPM score of 13.99. The evaluation indicates that the strategy is highly effective, with an effectiveness rate of 87.5%. Consequently, this strategy can be implemented through education, training, extension services, and stakeholder support to strengthen the group’s institutional capacity and enhance its self-reliance.